Knowledge And Perception The Among Dental Surgeons About A Periodontal Disease As A Risk Factor For Covid-19 Illness : A Web Based Questionnaire Study - Dr. P. Veerendranath Reddy,Dr. Chavva Lakshmi Charan Reddy, Dr. K. Phani Yasaswini, Dr. Ruparani Bodduru , Dr. B. Lavanya, Dr. Vijay V K. (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
INTRODUCTION: A Periodontal disease (PD) composes a group of diseases comprising inflammatory aspects of the host and dysbiotic events that impinge the periodontal tissues and could have systemic significances. Discrete factors and comorbidities have been closely accomplices with PD such as diabetes, aging, hypertension etc., although, elementary mechanisms or causal correlations have not been authorized completely. Fascinatingly, these same factors have been extensively correlated with progression of severely graded form of coronavirus disease 2019 (COVID-19), an illness caused by coronavirus SARS-CoV-2. Since inflammatory and dysbiotic factors as well as comorbidities impinge the systemic health, it is feasible that periodontal status illustrate the  possiblerisk of complications of COVID-19.AIMS:  To evaluate the Knowledge and perception among the dental surgeons about a Periodontal disease as a risk factor for covid-19 illness : a web based questionnaire study.SETTINGS AND DESIGN: A Questionnaire web based surveyMETHODS AND MATERIAL: Survey consists of 21 questions related to knowledge and awareness about corona virus and  periodontal disease as a  possible risk factor for covid-19 illness was conducted and evaluated using percentage among 312 participants (195 females 117 males).RESULTS: A total of 312 participants responded to the questionnaire. 67.1% had sufficient knowledge on the receptors that has high affinity for covid-19 disease, 81.7% dental surgeons had knowledge on periodontal disease that escalate risk for covid-19 related respiratory breakdown .46.8% and 21.9% had knowledge on pro inflammatory cytokine IL-6 and Th 17 enacts a considerablepart  in the pathogenesis of covid-19 and periodontitis.CONCLUSION: The study findings showed adequate awareness about corona virus and simultaneously showed inadequate awareness towards periodontal pathology as a hazardous factor for covid-19 illness among dental surgeons.